2018
DOI: 10.1097/aud.0000000000000494
|View full text |Cite
|
Sign up to set email alerts
|

Listening Effort: How the Cognitive Consequences of Acoustic Challenge Are Reflected in Brain and Behavior

Abstract: Everyday conversation frequently includes challenges to the clarity of the acoustic speech signal, including hearing impairment, background noise, and foreign accents. Although an obvious problem is the increased risk of making word identification errors, extracting meaning from a degraded acoustic signal is also cognitively demanding, which contributes to increased listening effort. The concepts of cognitive demand and listening effort are critical in understanding the challenges listeners face in comprehensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
452
3
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 457 publications
(476 citation statements)
references
References 130 publications
(139 reference statements)
15
452
3
6
Order By: Relevance
“…Indeed, prior to conducting this study, we expected to observe increased activity (e.g., in prefrontal cortex) for older adults relative to young adults, reflecting top-down compensation for reduced auditory sensitivity. Such activity would be consistent with increased cognitive demand during speech perception in listeners with hearing loss or other acoustic challenge (Pichora-Fuller et al, 2016;Peelle, 2018) . Although we were somewhat surprised not to see this, in retrospect, perhaps it would be expected.…”
Section: Discussionmentioning
confidence: 68%
“…Indeed, prior to conducting this study, we expected to observe increased activity (e.g., in prefrontal cortex) for older adults relative to young adults, reflecting top-down compensation for reduced auditory sensitivity. Such activity would be consistent with increased cognitive demand during speech perception in listeners with hearing loss or other acoustic challenge (Pichora-Fuller et al, 2016;Peelle, 2018) . Although we were somewhat surprised not to see this, in retrospect, perhaps it would be expected.…”
Section: Discussionmentioning
confidence: 68%
“…In everyday conversational contexts, we often communicate in challenging or adverse listening conditions. These listener‐related challenges can emerge because of external factors, such as noise (Peelle, ), but also because of internal factors, such as when communicating in a non‐native language (Lecumberri, Cooke, & Cutler, ). Everyday conversational contexts are often multimodal and can include auditory inputs, such as speech, but also visual input, such as visible speech and gestures.…”
Section: Introductionmentioning
confidence: 99%
“…Speech-in-noise recognition abilities are thought to rely (i) on additional cognitive resources that are recruited when recognising speech-in-noise (reviewed in Peelle, 2018) and (ii) on the fidelity of speech sound representation in brainstem nuclei, as measured by auditory brainstem response recordings (reviewed in . For example, studies investigating speech-in-noise recognition at the level of the cerebral cortex found networks that include areas pertaining to linguistic, attentional, working memory, and motor planning (Bishop and Miller, 2008;Salvi et al, 2002;Scott et al, 2004;Wong et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies investigating speech-in-noise recognition at the level of the cerebral cortex found networks that include areas pertaining to linguistic, attentional, working memory, and motor planning (Bishop and Miller, 2008;Salvi et al, 2002;Scott et al, 2004;Wong et al, 2008). These results suggest that during speech recognition in challenging listening conditions additional cerebral cortex regions are recruited that likely complement the processing of sound in the core speech network (reviewed in Peelle, 2018). The present study showed that besides the additional cerebral cortex region recruitment, a specific part of the sensory pathway is also modulated during speech-in-noise recognition, the left vMGB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation